Efficacy of Kangfuxin liquid for preventing and treating chemotherapy-induced oral mucositis: a systematic review and meta-analysis of randomized controlled trials - Sun, Wei; Jian, Yang; Feng, Xiaolin; Zhao, Minru; Liu, Yuan (Frontiers in Pharmacology, 2025)
ObjectiveChemotherapy-induced oral mucositis (CTOM) is a common side effect affecting 20%–40% of cancer patients receiving chemotherapy. Kangfuxin liquid (KFXL) has been used clinically to prevent and treat CTOM, but the evidence has not been systematically evaluated. This study aimed to evaluate the preventive and therapeutic effects of KFXL on CTOM.MethodsNine electronic databases were searched to identify KFXL-related randomized controlled trials (RCTs) for the prevention and treatment of CTOM from inception to September 2024. The primary outcomes were incidence rate, efficacy rate and cure rate, and the secondary outcomes was healing time.ResultsTwenty-one trials involving 1825 patients were included in this review. The results of our meta-analysis showed that, compared with basic oral care (BOC), KFXL significantly reduced the incidence rate of CTOM and severe CTOM (RR = 0.54, p < 0.00001; RR = 0.23, p < 0.00001, respectively), improved the efficacy rate of CTOM and severe CTOM (RR = 1.23, p = 0.0003; RR = 1.99, p = 0.05, respectively), improved the cure rate of CTOM (RR = 2.06, p = 0.0004),and accelerated the healing process (MD = −2.48, p < 0.00001). However, KFXL and other drugs have the same efficacy rate in treating CTOM and severe CTOM (RR = 1.00, p = 0.99; RR = 1.00, p = 1.00, respectively), and the same cure rate in CTOM (RR = 0.91, p = 0.39), and the same healing time (MD = −0.01, p = 1.00).ConclusionThe results suggest that KFXL may provide more benefit in the prevention and treatment for CTOM compared to BOC. Although KFXL may be a promising drug for the prevention and treatment of CTOM, the evidence is insufficient to prove its superiority over other guideline-recommended treatment.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024585859, ID: CRD42024585859.